Determinants of citizens' electronic participation: insights from India. Issue 3 (12th August 2014) - Alathur, Sreejith; Vigneswara Ilavarasan, P.; Gupta, M.P.
Abstract : Purpose: – The purpose of the present paper is to attempt to examine the determinants of citizens' electronic participation with respect to the communication aspects. To accomplish this objective, using the extant literature, the paper delineated factors that determine and the theories that can explain citizens' e-participation. An analysis of citizens' democratic communication through multiple e-participation forums is carried out, and the determinants of electronic participation are described in the paper. Design/methodology/approach: – In light of the literature, e-participation services were classified on the basis of characteristics of democratic communications. The factors that determine citizens' online democratic participation were also identified and validated. Indian citizens who often e-participate were surveyed through online and offline questionnaires. A regression analysis of the 407 responses was carried out to predict the influence of individual, governance and technology components on various e-participation initiatives. Findings: – Citizens' participation efficacy, value system and participation freedom were found to determine different e-participation initiatives. Further, e-participation is also found to be varyingly determined by the governance and technology components. Research limitations/implications: – The theoretical contribution of this study includes the classification of determining factors and the illustrative labeling (I, G and T) for an e-participation framework. The delineation of e-participation from democratic communication aspects also contributes to the e-participation literature. However, this research had considered only one set of e-participation services and had incorporated only select forms of e-participation that are in coherence with the services selected. Originality/value: – Past studies often consider separate e-participation forums and infrequently report a simultaneous analysis of multiple e-participation forums. The factors that determine citizens' e-participation from a democratic communication aspect are also inadequately discussed. The significant contribution of this study includes policy recommendations to improve e-participation in different information and communication technologies initiatives.